2020
DOI: 10.3390/ijerph17249392
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Profile of Tourists with a Greater Circular Attitude and Behaviour in Hotels of a Sun and Beach Destination

Abstract: This work aims to analyse the attitude towards circular economy (CE) and the environmental behaviour and circular practices among tourists of a well-known mature sun and beach destination. The study was conducted on a sample of tourists who visited Gran Canaria and stayed at a hotel establishment. Findings show that: (a) Older tourists have a higher pro-environmental or circular attitude in hotel establishments than younger ones; (b) most tourists are willing to pay more for environmentally friendly or green h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 84 publications
0
5
0
1
Order By: Relevance
“…As regards social items, several authors have investigated tourists and travelers’ behavior to achieve hotels’ sustainability. Rodrìguez et al (2020) have assessed that older tourists have a higher pro-environmental or circular attitude, highlight the importance to invest on energy-savings measures and increase tickets’ prices as well, although Julião et al (2020) have estimated that still few travelers are willing to pay extra costs. Further, Casado-Dìaz et al (2020) have discussed the role of gender towards sustainable practices, highlighting women as more virtuous in the field of water conservation behavior when on vacation.…”
Section: Resultsmentioning
confidence: 99%
“…As regards social items, several authors have investigated tourists and travelers’ behavior to achieve hotels’ sustainability. Rodrìguez et al (2020) have assessed that older tourists have a higher pro-environmental or circular attitude, highlight the importance to invest on energy-savings measures and increase tickets’ prices as well, although Julião et al (2020) have estimated that still few travelers are willing to pay extra costs. Further, Casado-Dìaz et al (2020) have discussed the role of gender towards sustainable practices, highlighting women as more virtuous in the field of water conservation behavior when on vacation.…”
Section: Resultsmentioning
confidence: 99%
“…However, the age categories used in the analysis have significant gaps, spanning approximately 17 years. Additionally, the study conducted by Rodríguez et al (2020) [38] confirmed that women are more likely than men to opt for green hotels, with women exhibiting more positive behavior in this regard [37,38]. Based on these findings from previous research and the need to update the landscape of green consumption in the demographic context, the hypothesis is proposed: Hypothesis H1.…”
Section: Demographic Profile In Customer Behavior and Trustmentioning
confidence: 80%
“…A study conducted in the Canary Islands found that older tourists (36 years and above) tend to have a stronger pro-environmental attitude when staying in hotel establishments compared to younger ones [38]. However, the age categories used in the analysis have significant gaps, spanning approximately 17 years.…”
Section: Demographic Profile In Customer Behavior and Trustmentioning
confidence: 99%
“…In turn, this connection can encourage sustainable tourist behavior. When tourists understand the importance of sustainable behavior and feel connected to the destination, they are more likely to engage in practices that promote sustainability, such as reducing waste, conserving energy, and supporting local businesses (Rodríguez et al, 2020). Continual promotional efforts can serve to further raise awareness and strengthen the connection between tourists and the destination, thereby reinforcing sustainable tourism practices (Roxas et al, 2020).…”
Section: Theoretical Value and Conceptual Frameworkmentioning
confidence: 99%